The associations between common neuroimaging parameters of Progressive Supranuclear Palsy in magnetic resonance imaging and non-specific inflammatory factors – pilot study - Alster, Piotr; Otto-Ślusarczyk, Dagmara; Kutyłowski, Michał; Migda, Bartosz; Wiercińska-Drapało, Alicja; Jabłońska, Joanna; Struga, Marta; Madetko-Alster, Natalia (Frontiers in Immunology, 2024)
Progressive Supranuclear Palsy is an atypical parkinsonism based on tauopathic pathology. Growing interest is associated with the pathomechanism of this disease. Among theories analyzing this issue can be mentioned the one highlighting the significance of inflammation. In this study authors examined 14 patients with PSP-Richardson syndrome (PSP-RS) and 13 healthy volunteers using laboratory testing based on the analysis of interleukins 1 and 6 (IL-1 and IL-6), tau in the cerebrospinal fluid (CSF) and non-specific parameters of peripheral inflammation in the serum (IL-1, IL-6, neutrophils, lymphocytes, monocytes, platelets and the ratios based on the factors). All of the patients underwent neuroimaging using magnetic resonance imaging using 3 Tesla. The serum levels of IL-1 were positively correlated with the area of the mesencephalon, suggesting that higher levels of IL-1 are not linked with atrophic changes in this region, whereas serum levels IL-6 was positively correlated with frontal horn width and negatively correlated with superior cerebellar area. Additionally IL-6 in the serum was found to be correlated with neutrophil-to-high density lipoprotein ratio. The observations were not confirmed in the analysis of the levels of interleukins in the CSF. To the best of our knowledge this work is one of the first analyzing this issue. The outcome of the work shows that the role of interleukins associated with microglial activation may possibly differ in the context of neurodegenerative changes, moreover the role of peripheral inflammation in PSP requires further analysis.